The Effect of Workload and Work Stress on Employee Performance at PT PLN (Persero) Customer Service Unit Karebosi City of Makassar - Karman; Chalid Imran Musa; Tenri S.P Dipoatmodjo; Siti Hasbiah; Uhud Darmawan Natsir (Economics and Business Journal (ECBIS), 2023)
This study was to determine the effect of workload and work stress on employee performance in PT PLN (Persero) Karebosi Customer Service Unit Makassar City. the sample of this study were 58 employees. This type of research is Quantitative research. The data used are primary data and secondary data obtained using the questionnaire distribution technique. The results of the study shows that there is a positive influence between the workload variable (X1) on employee performance (Y) and there is a negative influence between the work stress variable (X2) on the employee performance variable which can be shown through the multiple linear regression equation, namely Y = 38. 355 + 0.265 - 0.294 + e and has a significant effect with the t_ (calculated) value of each variable of 3.711> t_ (table) (X1) and -2.612> t_ (table) (X2), with a significance level of 0.003 <0.05 (X1) and 0.012 <0.05 (X2). The R Square value of 0.501 this figure shows that the workload variable and the work strea variable in this study contributed an influence of 50.1%.